The Moderating Role of Psychological Capital in the Relationship Between Workplace Ostracism and Turnover Intention - Rafi’ah, Khalidatul; Zamralita (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
Turnover intention , or employee intention to leave an organization, has become a significant concern in the modern workplace. This phenomenon can be detrimental to organizations by causing the loss of competent workers, increasing recruitment costs, and disrupting team productivity. One factor contributing to turnover intention is workplace ostracism , which is the exclusion or neglect experienced by individuals in the workplace. This study aims to examine the relationship between workplace ostracism and turnover intention, as well as the moderating role of psychological capital in this relationship. Workplace ostracism is defined as the neglect or ostracism experienced by individuals in the workplace. This study involved 288 employees from various industrial sectors in Indonesia, selected using a convenience sampling method. Data were collected through a questionnaire with standardized measuring instruments, including the Workplace Ostracism Scale, Turnover Intention Scale, and Psychological Capital Questionnaire (PCQ-24). The results showed a significant positive relationship between workplace ostracism and turnover intention (coefficient 0.77, p < 0.001), indicating that the higher the workplace ostracism, the greater the employee's intention to leave the organization. However, psychological capital was shown to moderate this relationship negatively and significantly, with a moderation coefficient of -0.10 (p < 0.001), so that high psychological capital can reduce the negative impact of workplace ostracism on turnover intention. This finding provides insights for organizations to address the impact of workplace ostracism by improving employee psychological capital. The practical implications of this study emphasize the importance of organizational strategies in creating an inclusive and supportive work environment, while also developing programs to strengthen employee psychological capital to effectively reduce turnover intention.